Pembiayaan Perumahan secara Musharakah Mutanaqisah di RHB Islamic Berhad (RHBIB): Analisis Kelebihan, Isu dan Cabaran dalam Penawaran Produk - Shuib, Mohd Sollehudin; Borhan, Joni Tamkin; Md Hussain, Muhammad Nasri (Academy of Islamic Studies, University Malaya Education Centre, 2011)
After using the contract of bay bithaman ajil (BBA) in financing products for a long time particularly home financing, Islamic banks in Malaysia has moved from a single contract to a hybrid instrument, from the debt financing to the form of equity financing. Through the debt financing, the customers are seen less supported and aided, and they are burdened and loaded as in the case of abandoned projects. Thus, hybrid instruments such as musharakah mutanaqisah is introduced to reduce customers risk. Muqassah approach or set-off approach is used in giving justice to the customers and also to the banks. The findings showed that Musharakah financing is better in terms of the validity of the contract and it has a few advantages that do not apply to the other contracts. Hence, the Islamic banking scholars need to further develop ideas and products that have not only sharia compliance, but also in line with the sharia base